The distribution of the activities in the behavior classification dataset. Horizontal axis presents frame index, vertical axis shows number of tracked bees assigned to one of the four behavior classes. Vertical lines separate five different records. The corresponding annotated frames with detected activities in these records are presented in Fig 12a, 12b, 12c, 12e, 12f, respectively. - Tomyslav Sledevič (20783469) (2025)
The distribution of the activities in the behavior classification dataset. Horizontal axis presents frame index, vertical axis shows number of tracked bees assigned to one of the four behavior classes. Vertical lines separate five different records. The corresponding annotated frames with detected activities in these records are presented in Fig 12a, 12b, 12c, 12e, 12f, respectively.